Rescuing the Danish Jews : a heroic story from the Holocaust - Byers, Ann (The Holocaust through primary sources, 2011)
"Examines the rescue of the Danish Jews during World War II, including background on Denmark and the Holocaust, firsthand accounts from the many people involved, and how thousands of Jews were saved from the Nazis"--Provided by publisher